Technical and Economical Feasibility Analysis on Household-Scale Rooftop Solar Power Plant Design with On-Grid System in Semarang City - Windarta, Jaka; Saptadi, Singgih; Denis; Satrio, Dimas Adi; Silaen, Johanes Soritua (Edelweiss Applied Science and Technology, 2021)
Utilizing rooftops as a solar power plant system on the grid can be an effective and efficient solution to reduce electricity bills. This research aims to design and analyze the potential of 1215 Wp solar power plant rooftop with on grid system household scale in terms of techno economy. Using each of the two alternatives to the main components of solar panels and inverters, there were 4 variations of the component configuration design in this study. Variation 1 uses Canadian solar panels with solax inverters. Variation 2 uses Canadian solar panels with so far inverters. Variation 3 uses risen solar panels with solax inverters. Variation 4 uses risen solar panels with sofar inverter. Through PVSyst 6.43 software, with an average radiation average of 5.48 kWh/m2/day, the potential energy production of each variation of 1215 Wp rooftop solar power plant household scale are 1873 kWh, 1893 kWh, 1865 kWh and 1885 kWh. The investment cost of 1215 Wp rooftop solar power plant ranges from IDR25,220,000-IDR27,020,000 with Net Present Value ranges from IDR15,309,805- IDR17,421,839, Benefit Cost Ratio ranges from 1,489- 1,588, Payback period ranges from 10.38 – 11.02 years and Internal Rate of Return value ranges from 8.8-9.56%.